Urgence Of Combined Claims Of Default And Branch Of Contract In Civil Procedure Law - Indah Siti Aprilia; Akhmad Budi Cahyono (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2022)
Lawsuits in civil law are divided into 2 (two) types, namely claims for breach of contract and lawsuits agains the law. In practice, many legal practitioners combine these 2 (two) basic claims in one lawsuit. This study uses a normative juridical method with the statue approach and case approach. The results of the study stated that a person is said be in default if he has fulfilled the achievements as stated in Article 1234 of Civil Code or as agreed then a person is considered to have committed an unlawful act if he fulfills the elements in 1365 of the Civil Code, and the party whose rights have been violated must prove that his rights have been violated and ask for compensation loss. Then in the doctrinal provisions, it is not permissible to mix up the claim for breach of contract as well as an act that violates the law, but if in formulating the posita it has been firmly separated between the fact of the act of default and the fact of the violating the law, then the merger is allowed. In addition, a default can at the same time lead to unlawful acts, as long as the fact is that it is afegault and the fact itself occurs outside the obligations required by the contract